1959
DOI: 10.1139/b59-021
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Fusarium Species in Canada: Vi. Taxonomy and Geographic Distribution of Fusarium Species on Plants, Insects, and Fungi

Abstract: The present investigation was commenced in 1932 and has been continued annually since that time with the object of determining the identity, host range, and geographic distribution of the Fz~sarizr?n species in Canada. Approximately 9000 isolates of Fzrsarizr?tz were studied. These isolates were obtained from 173 species and botanical varieties of plants, 14 species of insects, and 4 of fungi. Of the varlous specles and botanical varieties of plants from which isolates were obtained, 19 were cereals and grasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
7

Year Published

1962
1962
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 10 publications
2
13
0
7
Order By: Relevance
“…Contamination by mycotoxins makes barley unacceptable for malting and brewing (Beattie et al 1998;Salas et al 1999). (Abramson et al 1998;Clear et al 1996;Gordon 1959;McCallum et al 2000;Sturz and Johnston 1985). Of these species, F. graminearum is considered the most important causal agent of FHB in Canada (Clear et al 1996;Tekauz et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination by mycotoxins makes barley unacceptable for malting and brewing (Beattie et al 1998;Salas et al 1999). (Abramson et al 1998;Clear et al 1996;Gordon 1959;McCallum et al 2000;Sturz and Johnston 1985). Of these species, F. graminearum is considered the most important causal agent of FHB in Canada (Clear et al 1996;Tekauz et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium species are widely distributed in soil and on subterranean and aerial plant parts, plant debris, and other organic substrates (28,32,79,255). They are common in tropical and temperate regions and are also found in desert, alpine, and arctic areas, where harsh climatic conditions prevail (28, 32, 35, 59, 77, 78, 80, 92, 98, 110, 117, 162-164, 242, 251, 255).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that several Fusarium species have been isolated on a wide range of insects indicates that insects may also act as vectors (Miller et al, 1998). For example, mites have been reported to transport F. poae spores (Parry et al, 1995), and according to Gordon (1959), insects have been reported to carry…”
mentioning
confidence: 99%